Nursing perception of workload and professional growth - Arreaga Coello, Génesis; Carriel Lucas, Yulissa; Muñiz Granoble, Gloria; Rebolledo Malpica, Dinora (Revista Universidad de Guayaquil, 2023)
The workload in nursing is a common problem in this discipline, where not only the physical part but also the professional part is often affected, generating difficulties in the professional growth of this nursing group. The objective of the study was to determine the perception of nursing about workload and professional growth. Methodology was quantitative, correlational, the technique used in data collection was a survey previously validated by experts, applied to 100 nursing professionals working in health institutions in the city of Guayaquil, recognizing ethical consent, the data were worked with descriptive statistics. Results, it is possible to demonstrate that 52% expressed feeling exhaustion after their day, and 68% say that sometimes they have experienced stress in their workplace, unfortunately it is shown that only 13% of respondents have been able to participate in scientific updates and 66% that they are satisfied or that they consider that sometimes the payment is according to what they work. Conclusion, professional growth is largely determined by the perception of their satisfaction in their own performance.
Keywords: Nursing; overload; growth